Метод измерения среднеквадратического значения амплитудно-модулированного сигнала с промежуточным преобразованием напряжение-частота - Чинков, В. Н.; Гаврикова, Ю. А. (НТУ "ХПИ", 2010)
В статті розглянуто метод вимірювання середньоквадратичного значення амплітудно-модульованного сигналу з проміжним перетворенням напруга-частота. Проаналізовано завадозахищенність даного методу. Проведено оцінку похибки вимірювання, обумовленої наявністю завад. Показана структурна схема.

In article method of measurement root-mean-square values of the peak-modulated signal with preliminary transformation a voltage-frequency is considered. The noise immunity of the given method is analysed. The estimation of an error of the measurements brought by hindrances is made. The block diagramme is shown.
Keywords: носители информации; радиотехника; системы управления; уровни искажений; помехозащищенность; несущая частота